Long-term effects of kidney transplantation compared with dialysis on intima-media thickness in children - results from the 4C-T study - Grabitz, Carl Robert; Sugianto, Rizky; Doyon, Anke; Azukaitis, Karolis; Anarat, Ali; Bacchetta, Justine; Bayazit, Aysun K.; Bulut, Ipek K.; Caliskan, Salim; Canpolat, Nur; Düzova, Ali; Habbig, Sandra; et al. (Transplantation, 2024)
Background. - Children requiring kidney replacement therapy experience high burden of cardiovascular (CV) disease leading to increased mortality. Intima-media thickness (IMT) indicating atherosclerosis is a validated surrogate marker for future CV events. - Methods. - We investigated the effect of different treatment modalities (dialysis, preemptive kidney transplantation (KTx), late KTx after dialysis) on IMT by multivariable linear mixed-effect modeling. Patients were enrolled in a prospective cohort study. - Results. - A total of 261 analyzed children had a mean follow-up of 3 y. Children after preemptive and late KTx had lower levels of IMT when compared with dialysis. Using an interaction term, a significant progression of IMT over time was seen during dialysis (β = 0.0053 mm/y, P  =  0.004). IMT before the start of therapy was the most influential determinant in all models. Low IMT was associated with maintenance steroid treatment after preemptive KTx. High IMT on dialysis was associated with higher systolic blood pressure, lower body mass index, lower serum albumin, and lower bicarbonate. - Conclusions. - IMT remained rather stable in children several years after KTx. In contrast, children on dialysis had higher IMT values, which increased over time. In these children, blood pressure control, calorie and protein intake, and acid-base homeostasis seem important. Taken together, children might profit from early transplantation to limit accumulation of CV risk. - Export